EFL Students in English-Medium and EAP Courses in Turkey - Meltem Huri Baturay; Ahmet Erdost Yastibas (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
The present study aimed to determine university students’ perceptions regarding EM and EAP courses and how they studied EM and EAP courses and their exams. It was designed as a qualitative study. Eight students participated in the study. The data were collected through semi-structured interviews and analysed by content analysis method. The findings of the study indicated that the students who perform well in EM and EAP courses and who perform well in EM courses but have difficulty in EAP courses are motivated to receive EM courses and have positive attitudes toward EM courses. Yet, the students who perform well in EM and EAP courses are more motivated to receive EAP courses and have more positive attitudes toward EAP courses. The findings also indicated that the ways the students study EM and EAP courses and for their exams have both similarities and differences. The findings were discussed. The pedagogical implications and limitations of the study were explained, and suggestions for further research were made.